2020
DOI: 10.2478/ats-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional discriminant analysis of morphostructural traits in Nigerian locally adapted turkeys

Abstract: Association among biometric traits and characterisation based on sexed-plumage colour of Nigerian locally adapted turkey were investigated using discriminant analysis. Eight morphometric traits were measured to study their phenotypic variations between two plumage colours (Lavender and White). The characters measured were body weight (BW) as well as body dimensions such as wing length (WL), wing span (WS), body length (BL), breast girth (BG), shank length (SL), thigh length (TL) and keel length (KL) taken at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…It also finds consonance with the reports of Lan (2020), who observed that body length (0.616) strongly correlates with body weight in Muscovy ducks. It is also in congruence with Adenaike et al (2020), whose discriminant analysis of morphostructural parameters in locally adapted turkeys in Nigeria revealed a higher correlation between body length (0.91) and body weight. However, the work of Hailu et al (2018)…”
Section: Pearson Correlation Among Morphometric Traits Measuredsupporting
confidence: 72%
See 1 more Smart Citation
“…It also finds consonance with the reports of Lan (2020), who observed that body length (0.616) strongly correlates with body weight in Muscovy ducks. It is also in congruence with Adenaike et al (2020), whose discriminant analysis of morphostructural parameters in locally adapted turkeys in Nigeria revealed a higher correlation between body length (0.91) and body weight. However, the work of Hailu et al (2018)…”
Section: Pearson Correlation Among Morphometric Traits Measuredsupporting
confidence: 72%
“…On the contrary, ducks from the Rain forest recorded the longest wing span of 93.86cm, followed by the Semi-deciduous forest witnessing 93.17cm and the Coastal savanna, recorded 92.28cm. Adenaike et al (2020) and Bhowmik et al (2014) have conducted research to determine the wing span of turkey and Pigeons in Nigeria and Bangladesh, respectively, as influenced by sex and location, whereas Brown et al (2017) have studied the wingspan of both the local chicken and guinea fowl in Ghana and how the trait is influenced by agro-ecological zone and sex. However, there is no information on the wing span of ducks in the literature.…”
Section: Wing Spanmentioning
confidence: 99%
“…Models for predicting body weight with linear body measurements in the different genotypes were established using the Stepwise Multiple Linear Regression procedure of IBM SPSS (2011). The general linear model used was of the form in expression (1).…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of body weight with linear body measurements has been reported in cattle (Lukuyu et al 2016), sheep (Birteeb and Ozoje 2012), goats (Sam et al 2016) and various species of poultry. Most reports on chicken mainly focused on either pure breeds, crossbreds or mixed sexes (Gambo et al 2012;Ajayi et al 2008;Dzungwe et al 2018;Adenaike et al 2015) and not on combinations of genotypes, sexes and ages in chicken. Moreover, many authors who predicted body weight from linear body measurements of chickens used the entry method of multiple linear regression analysis (Ukwu et al 2014; Nosike et at.…”
Section: Introductionmentioning
confidence: 99%
“…En México, es mínima la información relativa a la variabilidad genética y fenotípica de las poblaciones caprinas locales (Dorantes-Coronado et al, 2015). Este tipo de estudios proporciona una representación sólida de la variabilidad entre razas y brinda información útil sobre la aptitud productiva de los animales y su relación genética con las medidas corporales que han sido influidas por el ambiente en que se desarrollan, por lo que el desconocimiento de estas características deriva en modelos animales incompatibles con la producción (Bravo y Sepúlveda, 2010;Adenaike et al, 2020). Cabe señalar que la variabilidad genética en todas las especies es sumamente valiosa para asegurar que los animales puedan hacer frente a las condiciones ambientales (Ojo et al, 2015).…”
Section: Introductionunclassified